Northern tropical Indian Ocean Mg/Ca derived SST for the last glacial termination, sediment core SSD004_GC03 - Dharmendra Pratap Singh; Rajeev Saraswat; Mahyar Mohtadi; Pankaj Kumar (PANGAEA, 2021)
Here, we reconstructed sea surface temperature (SST) and upwelling intensity record from the northern tropical Indian Ocean for the last glacial termination (8-24 kyr BP). The marine sedimentary archive was collected during forth voyage of ORV Sindhu Sadhana and SST record was reconstructed using Mg/Ca in G. ruber white (sensu stricto). The upwelling intensity was reconstructed using percentage abundance of G. bulloides. The record demonstrates that the northern tropical Ocean began warming well before the increase in the atmospheric carbo dioxide and has potential implications for the strengthening of the AMOC as well as the eventual glacial termination.